Vietnamese EFL Lecturers’ Perceptions of the Role of ChatGPT in Facilitating Language Acquisition Among Their Students - Le, Thanh Thao; Yen, Phuong Hoang; Pham, Trut Thuy; Tran, Ngoc Bao Chau; Nguyen, Thi Thuy Linh (Journal of educational technology development and exchange, 2025)
This qualitative study investigates the perceptions of Vietnamese EFL teachers regarding the role of ChatGPT in Second Language Acquisition (SLA). Amidst the growing integration of Artificial Intelligence (AI) in education, this research focuses on understanding how educators at different career stages perceive the effectiveness of ChatGPT in enhancing language learning experiences. Employing semi-structured interviews, the study engaged nine teachers from two educational institutions in Vietnam. Thematic analysis, guided by the Technology Acceptance Model (TAM) and the Constructivist Theory of Learning, revealed multiple roles of ChatGPT in SLA. These include its use as a conversational partner, a tool for immediate feedback, a facilitator of cultural exposure, and an enhancer of linguistic competence. Additionally, ChatGPT was recognized for supplementing traditional teaching methods, encouraging self-directed learning, personalizing learning experiences, and providing diverse language exposure. Further roles included bridging communication gaps, simulating real-world scenarios, and fostering continuous learning, motivation, and engagement. The study highlights the potential of AI tools like ChatGPT to transform language teaching methodologies, offering more interactive, engaging, and personalized learning experiences. This study contributes valuable insights into the evolving landscape of technology-enhanced language education and the roles AI can play in enriching SLA practices.